Effectiveness of interpretive panels at Sarawak Cultural Village, Malaysia - Abi, Jane (2018)
The purpose of this study was to evaluate the effectiveness of existing nonpersonal culture interpretation product of the 7 ethnic houses at Sarawak Cultural Village, Kuching. The results were obtained from a total of 700 respondents divided into control and treatment groups. The Tilden’s Interpretation Principles, Theory of Reasoned Action (TRA) and Triadic Model of Attitude were used to determine the effectiveness of existing messages and when subjected with interpretive intervention. A set of interpretive messages were designed using the Tilden’s Interpretation Principles and were introduced to respondents in the treatment group. Meanwhile, the existing interpretation messages were included in the questionnaire distributed to the respondents in the control group. Based on the results, the control group respondents found themselves not attracted to read the existing messages. Most of the respondents commented they are more interested in illustrative messages. They claimed that the existing message was too long, and its content lacks segmentation/ paragraph. They are unable to recall the message after reading and will not read all of the messages at the ethnic houses. As a result, the respondents do not fully understand the culture, less aware and lose interest to participate in the cultural activity provided. Similarly, the respondents in the treatment group are more interested in illustrative messages. A higher percentage of the respondents were attracted to read the messages and they can recall the cultural information that they have read. They also have a higher appreciation of the ethnic’s culture. This was evident in the findings where they have higher percentage of admiration and appreciation of the various ethnics’ cultures. The respondents also showed a higher percentage in the willingness to disseminate the ethnic’s culture, excited to participate in more cultural events and contribute to the conservation of culture preservation as a whole. The results of this study proved that messages with interpretive intervention are more effective in attracting visitors and influence them in accepting the knowledge while having emotional impacts to enhance the effectiveness of messages provided at cultural tourism sites. In terms of physical characteristics of the message panels, respondents also suggested several criteria that will make the displayed messages more appealing to the public. It appeared that the message panels’ position, height, material, typeface, font type and size, as well as graphic design contribute to the holding power and attract respondents to read the messages, affectively effected and willingness to participate in cultural heritage-based activities and programs. Therefore, it is recommended that the non-personal cultural interpretive panels undergo a facelift. More thoughtful and attractive interpretive message designs will also attract visitors to use the non-personal interpretation facility. It will consequently lead to an increase in awareness, appreciation, participation and sustainability of cultural heritage tourism, especially at Sarawak Cultural Village.